Mountain Sisters : From Convent to Community in Appalachia - Lewis, Helen Matthews (Book collections on Project MUSE., 2003)
Monica Appleby and Helen Lewis reveal the largely untold story of women who stood up to the Church and joined Appalachians in their struggle for social justice. Their poignant story of how faith, compassion, and persistence overcame obstacles to progress in Appalachia is a fascinating example of how a collaborative and creative learning community fosters strong voices. Mountain Sisters is a prophetic first-person account of the history of American Catholicism, the war on poverty, and the influence of the turbulent 1960s on the cultural and religious communities of Appalachia. Founded in 1941,